The Impact of Climbing Sports toward Socio-Cultural Change in Promasan Hamlet, Limbangan District, Kendal Regency, Central Java - Pramadanus, Imam; Setyawati, Heny; Soenyoto, Tommy (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
As one of the hamlets under the foot of Mount Ungaran, the Promasan Hamlet community must be able to accept social and cultural changes that occur due to the arrival of climbers, the purpose of this study is to review and analyze sports values ​​that occur in the Promasan Hamlet community, to review and analyze the impact of climbing sports on the Promasan Hamlet social community, to review and analyze the impact of climbing sports on the culture of the Promasan Hamlet community. This study used qualitative research methods. The research approach used ethnography. Data collection techniques used observation, interviews, and documentation. The data validity technique used data triangulation. Data analysis techniques used interactive analysis. The findings of this study are the existent of sports values ​​include: leadership, self-confidence, discipline, cooperation, honesty, sportsmanship, responsible for the activities and activities of the community and climbers, social changes occur include: social structure and social interaction in Promasan Hamlet, Cultural changes include: lifestyle in Promasan Hamlet. This study concluded that the presence of climbers or migrants in Promasan Hamlet causes social and cultural changes and the existence of sports values ​​in every event and activity of the community and climbers. Suggestions to the local government should pay more attention to the hamlet community.